Suspected scaphoid injuries managed by MRI direct from the emergency department: a single-centre prospective cohort study. (1st June 2021) - Dean, Benjamin J. F.; Little, Christopher; Riley, Nicholas D.; Sellon, Edward; Sheehan, Warren; Burford, Jenna; Hormbrey, Phil; Costa, Matthew L.
Abstract : Aims: To determine the role of early MRI in the management of suspected scaphoid fractures. Methods: A total of 337 consecutive patients presenting to an emergency department (ED) following wrist trauma over a 12-month period were prospectively included in this service evaluation project. MRI was not required in 62 patients with clear diagnoses, and 17 patients were not managed as per pathway, leaving a total of 258 patients with normal scaphoid series radiographs who were then referred directly from ED for an acute wrist MRI scan. Patient demographics, clinical details, outcomes, and complications were recorded at a minimum of a year following injury. Results: The median time from injury to ED presentation was one day and the median number of positive clinical signs was two out of three (snuffbox tenderness, tubercle tenderness, pain on telescoping). Of 258 patients referred for acute MRI, 208 scans were performed as 50 patients either did not tolerate (five patients) or did not attend their scan (45 patients). MRI scans demonstrated scaphoid fracture (13%), fracture of another bone (22%), scaphoid contusion (6%), other contusion/ligamentous injury (20%), or solely degenerative pathology (10%). Only 29% of scans showed no abnormality. Almost 50% of those undergoing MRI (100 patients) were discharged by ED with advice, with only one re-presentation. Of the 27 undisplaced occult scaphoid fractures, despite prompt cast immobilization, two experienced delayed union which was successfully treated with surgery. Conclusion: The use of MRI direct from ED enables prompt diagnosis and the early discharge of a large proportion of patients with normal radiographs following wrist trauma. Cite this article: Bone Jt Open  2021;2(6):447–453.